Diversity of natural dye plants in The Taplel Waterfall Area, Sisimeni Sanam Training Forest, Takari District, Kupang District - Sabuna, Alan; Hendrik, Arnold Christian; Rafael, Andriani; Nge, Sonya Titin; Ngginak, James (Foresty Faculty of Hasanuddin University, 2023)
The Taplel waterfall area which is in the Sisimeni Sanam Education and Training Forest area is one of the conservation areas in East Nusa Tenggara which has quite high biodiversity, including plants that produce natural colors. However, information on the species diversity of dye plants in the Taplel waterfall area is still lacking. The objective of this study was to uncover the diversity of natural dye plants in the Taplel waterfall area, Sisimeni Sanam Training Forest, Takari District, Kupang Regency. Data collection was carried out by setting sample plots measuring 2 x 2 meters (seedlings), 5 x 5 meters (saplings), 10 x 10 meters (poles), and 20 x 20 meters (trees). Analysis of the importance of species using the Importance Value Index, and species diversity using the Species Diversity Index (Shannon-Wiener Index). Species of natural dye plants found in the Taplel Waterfall Area include Tectona grandis, Cassia siamea, Acacia auriculiformis, Tamarindus indica, Ficus racemosa, Leucaena leucocephala, Schleichera oleosa, Bauhinia purpurea, Cassia fistula, Garuga floribunda, and Annona squamosa L.. Plant species that has the highest important role in the Taplel Waterfall Area is Cassia fistula (sapling), Bauhinia purpurea (pole), and Tectona grandis (tree). Meanwhile, the diversity of natural dye plant species in the Taplel Waterfall Area at the level of seedlings, saplings, poles and trees is in the moderate category.